2022
DOI: 10.1093/pm/pnac069
|View full text |Cite
|
Sign up to set email alerts
|

Pain Location and Exacerbating Activities Associated with Treatment Success Following Basivertebral Nerve Ablation: An Aggregated Cohort Study of Multicenter Prospective Clinical Trial Data

Abstract: Objective Develop pain location “maps” and investigate the relationship between low back pain (LBP)-exacerbating activities and treatment response to basivertebral nerve radiofrequency ablation (BVN RFA) in patients with clinically suspected vertebral endplate pain (VEP). Design Aggregated cohort study of 296 patients treated with BVN RFA at 33 centers in three prospective trials. Methods Participant demographics, pain diagrams, and LBP-exace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…We do recognise that having published their review protocol in Prospero they had limited freedom to do so. Unfortunately, Herlin et al is often being inappropriately cited as demonstrating no association between LBP and MC without acknowledging its limitations [30][31][32][33][34][35][36][37][38], but others do cite it in a more appropriate nuanced way [23,[39][40][41][42][43][44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We do recognise that having published their review protocol in Prospero they had limited freedom to do so. Unfortunately, Herlin et al is often being inappropriately cited as demonstrating no association between LBP and MC without acknowledging its limitations [30][31][32][33][34][35][36][37][38], but others do cite it in a more appropriate nuanced way [23,[39][40][41][42][43][44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Papers citing Herlin et al were identified using Pub-Med [23,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. The literature was searched through PubMed with the keywords "MRI (back pain) association Modic" restricted to the last 5 years and identified 135 articles.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations